Застосування геш-хамелеону у протоколах електронного цифрового підпису на основі білінійних відображень у системах на ідентифікаторах - Погребняк, К. А.; Іщенко, Ю. М. (ХНУРЭ, 2009)
The advantages of deployment of Identity-Based Systems and Hash-Chameleons are considered. The analysis of protocols of signatures with Hashchameleon based on using bilinear maps was made.